Malaysia’s role in invigorating Nam’s Bandung spirit - Kamarulnizam Abdullah, (Penerbit UKM, 2013)
It has been argued that the end of the Cold War signaled the waning influence of Non-Align Movement (NAM). NAM had been considered a third force during the Cold War rivalry between two superpowers but after the war the movement appeared to lose its momentum and failed to achieve the aspirations of the Bandung Spirit conference of 1955, which called for political cooperation among newly independent Asian and African countries. This article discusses to what extent the Bandung spirit continues to inspire the NAM’s struggle for self-respect and self-determination among developing countries post-Cold War and analyses the major challenges NAM faces in reviving its status as a respected international organization representing developing countries in the current unipolar international political system. Finally, the article explores Malaysia’s part in reinvigorating the Bandung spirit among NAM member countries since the 1997 Kuala Lumpur Summit.